A framework for preferred practices in conducting culturally competent health research in a multicultural society - Lisa Woodland; Ilse Blignault; Cathy O'Callaghan; Ben Harris-Roxas (BMC, 2021)
Abstract Background Improving the health and well-being of the whole population requires that health inequities be addressed. In an era of unprecedented international migration, meeting the health care needs of growing multicultural or multiethnic societies presents major challenges for health care systems and for health researchers. Considerable literature exists on the methodological and ethical difficulties of conducting research in a cross-cultural context; however, there is a need for a framework to guide health research in multicultural societies. Methods The framework was informed by "research on research" that we have undertaken in community and primary health care settings in Sydney, Australia. Case studies are presented as illustrative examples. Results We present a framework for preferred practices in conducting health research that is culturally informed, high-quality, safe, and actionable. Conclusions The framework is not intended to be universal, however many of its aspects will have relevance for health research generally. Application of the framework for preferred practices could potentially make health research more culturally competent, thus enabling enhanced policies, programmes and practices to better meet population health needs. The framework needs to be further tested and refined in different contexts.